Smart Nanofibers with Natural Extracts Prevent Senescence Patterning in a Dynamic Cell Culture Model of Human Skin - Bellu, Emanuela; Garroni, Giuseppe; Cruciani, Sara; Balzano, Francesca; Serra, Diletta; Satta, Rosanna; Montesu, Maria Antonia; Fadda, Angela; Mulas, Maurizio; Sarais, Giorgia; Bandiera, Pasquale; Torreggiani, Elena; et al. (Cells, 2020)
Natural cosmetic products have recently re-emerged as a novel tool able to counteract skin aging and skin related damages. In addition, recently achieved progress in nanomedicine opens a novel approach yielding from combination of modern nanotechnology with traditional treatment for innovative pharmacotherapeutics. In the present study, we investigated the antiaging effect of a pretreatment with Myrtus communis natural extract combined with a polycaprolactone nanofibrous scaffold (NanoPCL-M) on skin cell populations exposed to UV. We set up a novel model of skin on a bioreactor mimicking a crosstalk between keratinocytes, stem cells and fibroblasts, as in skin. Beta-galactosidase assay, indicating the amount of senescent cells, and viability assay, revealed that fibroblasts and stem cells pretreated with NanoPCL-M and then exposed to UV are superimposable to control cells, untreated and unexposed to UV damage. On the other hand, cells only exposed to UV stress, without NanoPCL-M pretreatment, exhibited a significantly higher yield of senescent elements. Keratinocyte-based 3D structures appeared disjointed after UV-stress, as compared to NanoPCL-M pretreated samples. Gene expression analysis performed on different senescence associated genes, revealed the activation of a molecular program of rejuvenation in stem cells pretreated with NanoPCL-M and then exposed to UV. Altogether, our results highlight a future translational application of NanoPCL-M to prevent skin aging.
Keywords: proliferace buněk; keratinocyty; Skin Aging; Stem Cells; nanovlákna; Keratinocytes; Fibroblasts; rostlinné extrakty; lidé; stárnutí buněk; Ultraviolet Rays; kmenové buňky; Nanofibers; kůže; fibroblasty; kultivované buňky; Polyesters; Myrtus; Cells, Cultured; Skin; Cell Proliferation; Plant Extracts; exprese genu; stárnutí kůže; polyestery; Cellular Senescence; Gene Expression; ultrafialové záření; Humans